MR and CT techniques - Dias, João Lopes; Cunha, Teresa Margarida (Springer Berlin Heidelberg, 2017)
Magnetic resonance imaging (MRI) and computed tomography (CT) are routinely used in female pelvis imaging. MRI is primarily useful for locoregional characterization of benign and malignant diseases. CT is less accurate in locoregional evaluation, but remains useful in the follow-up of treated gynecological malignancies, as well as in the setting of emergency and in the guidance of biopsies. Although transabdominal and transvaginal ultrasonography (US) is not under the scope of this chapter, it remains the first-line imaging method for most gynecological conditions.